Building Trust : Developing the Russian Financial Sector - World Bank (Washington, DC, 2013)
This book examines progress within Russia's financial sector and provides a road map for promoting dialogue on and implementing improvements. The book is intended to complement and support the joint strategic plan of Russia's government and Central Bank for banking reform, a plan that includes many already-implemented legislative and regulatory efforts aimed at strengthening the Russian financial sector as a whole. The authors contend that any comprehensive strategy designed to enhance trust in Russian banking will need to focus on four major themes: 1) encouraging financial intermediation by improving the legal and accounting infrastructure for financial sector development; 2) improving the current structure and performance of the banking system; 3) improving the effectiveness of bank regulation, bank restructuring, and liquidation; and 4) enhancing enterprise access to finance.